Fish Assemblages In Kerian River Tributaries, Kedah – Perak Border - Zakeyuddin, Mohd. Shafiq (2012)

(untitled)
Influence of habitat characteristics on fish distribution in selected Kerian River tributaries was investigated from May 2008 to June 2009 by measuring several physico-chemical parameters; DO, pH, temperature, salinity, conductivity, TDS, velocity, river depth and width. Mean DO content in the water, ion conductivity, water temperature, TDS content, water velocity, river width and depth were significantly different among rivers (Kruskal-Wallis Test, P < 0.05). Forty eight fish species from 20 families were collected using a cast net, an electrofishing and an insect net.